Study on 4-Formyloxime-3-Methyl-1-(2´ ,4´ -Dinitrophenyl)-2-Pyrazolin-5-one as a Gravimetric Reagent for Co(II), Ni(II) and Cu(II) - J. Kharodawala, Mohammad; K. Rana, Arjun (Asian Journal of Chemistry, 2010)
4-Formyloxime-3-methyl-1-(2',4' -dinitrophenyl)-5-one can be used as a gravimetric' reagent for Co(ll). Ni(ll) and Cu(ll). An attempt has been made to determine (a) Cu(II) and Ni(II) (b) Cu(ll) and Co(II) from their binary mixture at selective pH value. The estimation of Co(ll), Ni(lI) and Cu(II) metal ions in the presence of different metal ions such as Sr(II), Ca(ll), Cd(II), AI(III), Ba(lI) and Mg(II) has also been carried out. Such interfering metal ions failed to respond.